The benefits of being economics professor A (and not Z) - C. Mirjam van Praag; Bernard M. S. van Praag (Center for Economic Studies and ifo Institute (CESifo), 2007)
Alphabetic name ordering on multi-authored academic papers, which is the convention in the economics discipline and various other disciplines, is to the advantage of people whose last name initials are placed early in the alphabet. As it turns out, Professor A, who has been a first author more often than Professor Z, will have published more articles and experienced a faster growth rate over the course of her career as a result of reputation and visibility. Moreover, authors know that name ordering matters and indeed take ordering seriously: Several characteristics of an author group composition determine the decision to deviate from the default alphabetic name order to a significant extent.
Keywords: A11; A14; J32; J44; 330; performance measurement; incentives; economists; name ordering; Wirtschaftswissenschaftler; Prestige; Publikationsanalyse; Schätzung; Welt